Mechanism of dexmedetomidine protection against cisplatin induced acute kidney injury in rats - Zeng-lu Zheng; Jun-wei Ma; Yi Luo; Gui-jin Liang; Shi-jie Lei; Ke-jin Yan; Hai-bing Meng; Xiu-juan Liu (Renal Failure)
Objective This study explored the molecular mechanisms by which dexmedetomidine (Dex) alleviates cisplatin (CP)-induced acute kidney injury (AKI) in rats.Methods CP-induced AKI models were established, and Dex was intraperitoneally injected at different concentrations into rats in the model groups. Subsequently, rats were assigned to the control, CP, CP + Dex 10 μg/kg, and CP + Dex 25 μg/kg groups. After weighing the kidneys of the rats, the kidney arterial resistive index was calculated, and CP-induced AKI was evaluated. In addition, four serum biochemical indices were measured: histopathological damage in rat kidneys was detected; levels of inflammatory factors, interleukin (IL)-1β, IL-18, IL-6, and tumor necrosis factor alpha, in kidney tissue homogenate of rats were assessed through enzyme-linked immunosorbent assay (ELISA); and levels of NLRP-3, caspase-1, cleaved caspase-1, gasdermin D (GSDMD), and GSDMD-N in kidney tissues of rats were determined via western blotting.Results Dex treatment reduced nephromegaly and serum clinical marker upregulation caused by CP-induced AKI. In addition, hematoxylin and eosin staining revealed that Dex treatment relieved CP-induced kidney tissue injury in AKI rats. ELISA analyses demonstrated that Dex treatment reduced the upregulated levels of proinflammatory cytokines in the kidney tissue of AKI rats induced by CP, thereby alleviating kidney tissue injury. Western blotting indicated that Dex alleviated CP-induced AKI by inhibiting pyroptosis mediated by NLRP-3 and caspase-1.Conclusion Dex protected rats from CP-induced AKI, and the mechanism may be related to NLRP-3/Caspase-1-mediated pyroptosis.